XIAO-CHAI-HU TANG IN TREATING MODEL MICE WITH D-GALACTOSAMINE-INDUCED LIVER INJURY - Zhou, Yun-Xiao; Qiu, Yun-Qing; Xu, Li-Qian; Guo, Jing; Li, Lan-Juan (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
This study explored the effects of a classical Chinese medicine formula- Xiao-Chai-Hu Tang(XCHT) on the model mice with D-galactosamine -induced liver injury. Sixty male imprinting control region (ICR) mice were used in the present study, and they were separated randomly into 6 groups: a normal control group (Group A, n=10), a model control (Group B, n=10), a positive control (Group C, n=10), a low dose of XCHT group (Group D, n=10), a medium dose of XCHT group (Group E, n=10), and a high dose of XCHT group (Group F, n=10). ELISA was used to detect the IL-6 and TNF-Î± levels in the serum. Real-time PCR was performed to assess the expression of FasmRNA, Fas-LmRNA, Bcl-2mRNA of the liver tissues. Western blotting was used to detect the Bax protein expression of the liver tissues. The serum IL-6 and TNF-Î± levels of Group B were significantly higher than the other groups (P<0.05). The expression of Fas mRNA, Fas-LmRNA, and Bax protein of the liver tissues of Group B were significantly higher than those of the other groups (P<0.05). The expression of Bcl-2 mRNA of the liver tissues of Group B was significantly lower than other groups (P<0.05). Both of XCHT and biphenyl dicarboxylate significantly decreased the serum IL-6 and TNF-Î± levels and FasmRNA, FasLmRNA, Bax protein expression and increased the Bcl-2 mRNA expression of the liver tissues of model mice (P<0.05). It may be through decreasing the serum IL-6 and TNF-Î± levels and FasmRNA, FasLmRNA, Bax protein expression and increasing the Bcl-2 mRNA expression of the liver tissues that XCHT significantly relieved the D-galactosamine -induced liver injury.